Estudio termográfico en la subestación Puyo y el alimentador circunvalación de la EEASA para el análisis de cargabilidad en el periodo 2014 - Bernal Reyes, Paúl Alejandro (2015)
This research presents the summary of a systematic means for thermography testing on some elements of the substation and feeder. It was applied at Ambato SA Electric Company. Itisa proposal toget a solution to the problem offered by the maintenance unit of the company. This is a consequence as lack of a procedure that allows the peoplewho works in the unit. It provides a theoretical and practical tool and effectively and efficiently instrument maintenance work in substations and feeders. This relate thermography technique with the chargeability specifically transformers....